2021
DOI: 10.1098/rsos.211108
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for quantifying epithelial and stromal thickness changes after orthokeratology contact lens wear

Abstract: The aim of the study was to develop an automatic segmentation approach to optical coherence tomography (OCT) images and to investigate the changes in epithelial and stromal thickness profile and radius of curvature after the use of orthokeratology (Ortho-K) contact lenses. A total of 45 right eyes from 52 participants were monitored before, and after one month of, uninterrupted overnight Ortho-K lens wear. The tomography of their right eyes was obtained using optical OCT and rotating Scheimpflug imaging (OCULU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The RPC in Ortho-K, believed to be achieved by epithelial thinning in the central cornea and thickening towards the periphery, has associated biological and mechanical risks. Clinically, there is a risk of reducing resistance to microbial infection by weakening the central epithelial barrier [9,10,[66][67][68][69]. From the mechanical point of view, lens-eye interactions can result in variable visual results due to residual refractive error [70].…”
Section: Discussionmentioning
confidence: 99%
“…The RPC in Ortho-K, believed to be achieved by epithelial thinning in the central cornea and thickening towards the periphery, has associated biological and mechanical risks. Clinically, there is a risk of reducing resistance to microbial infection by weakening the central epithelial barrier [9,10,[66][67][68][69]. From the mechanical point of view, lens-eye interactions can result in variable visual results due to residual refractive error [70].…”
Section: Discussionmentioning
confidence: 99%
“…Increased min-max has been reported by some studies [ 180 , 184 ], particularly in OK lens users for more than two weeks [ 184 ]. Although some studies reported a significant increase in the corneal stromal thickness after OK lenses [ 91 , 181 ], there was no significant change in stromal posterior surface radii of curvature [ 181 ], and the refractive changes after OK were caused mainly by changes in CET and anterior stromal curvature and not correlated with stromal thickness alteration [ 91 , 181 ].…”
Section: Contact Lens Usementioning
confidence: 99%
“…Alterations in the ETM profle associated with OK lenses in treating low-to-moderate myopia (<5 diopters) and <1.5 diopters of astigmatism have been investigated. In the central 2 mm zone, almost all studies have reported decreased central CET after the use of OK lenses for myopic eyes [6,29,91,148,[180][181][182][183][184][185]. Regarding the paracentral region (2-5 mm), results are less consistent; diferent fndings from diferent studies suggest no signifcant change [180], signifcant decreases in thickness in temporal [6,181,184], nasal [181], and inferior sectors [184], nonsignifcant increase in CET along the vertical meridian [181], and signifcant thinning in the paracentral zone with more prominence in temporal and inferior sectors [91].…”
Section: Orthokeratology (Ok)mentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Changes in stromal thickness after wearing the ortho-k lenses were inconsistent in different studies, 15–17 and the anterior and posterior stromal curvature radii did not change significantly. 18 Therefore, the shape of the epithelium after ortho-k treatment is important for evaluating the efficacy of lenses.…”
mentioning
confidence: 99%